A Case Report of Small Bowel Feces Sign (Bangladesh Journal of Radiology and Imaging, 2026)
The small bowel feces sign is observed on abdominal CT scans which is a sign of decreased small bowel motility and has been described as a finding indicative of small bowel obstruction (SBO) or another severe small-bowel abnormality (e.g. metabolic or infectious disease). Recognition of this sign is important and helpful to locate the level of obstruction.BJRI, 2024; VOL. 32(2): 139-141